Patients' experiences of health and social care in long-term neurological conditions in England: A cross-sectional survey. (January 2013) - Peters, Michele; Fitzpatrick, Ray; Doll, Helen; Playford, E Diane; Jenkinson, Crispin
Objectives: To investigate patients' experiences of health and social care services in long-term neurological conditions in England. Method: Cross-sectional survey of 5209 patient members of the Motor Neurone Disease Association (MND, n = 890), Multiple Sclerosis Society (MS, n = 2345) or Parkinson's UK (PD, n = 1974). A questionnaire on patient experiences of health and social care was completed by 2563 (49%) (505 MND, 1157 MS and 901 PD). Results: A mixed picture of experiences of health and social care in MND, MS or PD was found with few problems reported for some aspects of services such as obtaining information about medication (n = 117, 6.1%). In contrast, problems with planning and integration of care were reported frequently, with 78.0% of patients not having a care plan and 61.9% reporting that services do not collaborate well in planning care. Other problems included delays with diagnosis, information about medication side effects, and management of conditions whilst in hospital. Significant differences between the three conditions were found for most aspects of care, with MND patients generally reporting fewer problems. The findings highlight which areas of health and social care need to be improved and monitored. While a larger sample size was obtained than in other studies, possible limitations include the sampling frame and the 49% response rate. Conclusion: Planning and integration of care are key areas that require improvement.